Modelagem da capacidade de transporte de sedimentos em latossolo férrico - Costa, Jacqueline Tonielo da [UNESP] (2015)
The sediment transport capacity (Tc), the erodibility in grooves (Kr) and the critical shear stress of the soil (c) are used in many prediction of erosion, as the WEPP - Water Erosion Prediction Project. The objective of this study was to propose, calibrate and evaluate equations, such as Yalin and simplified FINKNER, to determine the sediment transport capacity and, consequently, the erodibility in grooves and the critical shear stress of an Oxisol clayey. The results provided that equations to estimate the sediment transport capacity (Tc) as a function of the flow shear stress, are more efficient for predicting Tc Latossol to study compared with equations that consider the power flow. The equation Yalin allowed to estimate Tc and set values for the erodibility in grooves and critical shear stress. For Rhodic Latosol clay texture, breakdown rates were linear with the shear stress, and the erodibility value in grooves (Kr) was 0.0025 kg N-1 s-1 and the critical shear stress (c) was 2.560 N m-2